IMPLEMENTASI KURIKULUM MERDEKA DALAM MENINGKATKAN MINAT DAN BAKAT PESERTA DIDIK DENGAN PROGRAM P5 DI TINGKAT SEKOLAH MENENGAH ATAS - Ferdiana, Ferdiana; Riris Idiawati; Maya Nur Khasanah (JEAS (Journal of Educational and Applied Science), 2025)
The Merdeka Curriculum is an education reform designed to address inequalities in the quality of education in Indonesia. It emphasizes flexible, contextual and student-centered learning, with a focus on character development, 21st century skills and technology integration. Teachers act as facilitators who assist students to be active and independent. Although it provides room for innovation, its implementation still faces challenges, especially in 3T areas. The success of Merdeka Curriculum depends heavily on the synergy between the government, schools, teachers, parents, and communities as well as continuous evaluation and training, and to improve our interests and talents using P5 subjects. The research method used is qualitative. The research objective is to find out the implementation of the independent curriculum to increase students' interests and talents with the P5 program. The results of the research on the Implementation of the Independent Curriculum at SMA Negeri 1 Muncar show positive progress in creating active, independent, and contextualized learning. Through the collaboration of teachers, students, and school management, as well as the support of the P5 program, this curriculum encourages the development of students' character and creativity. Despite facing challenges such as limited facilities and adaptation of learning culture, strategic efforts such as training, regular reflection, and participatory leadership are the keys to success in implementing this curriculum in a sustainable manner.